2006
DOI: 10.1007/s00410-006-0141-0
|View full text |Cite|
|
Sign up to set email alerts
|

Preservation of Fe isotope heterogeneities during diagenesis and metamorphism of banded iron formation

Abstract: We present the iron isotope composition of primary, diagenetic and metamorphic minerals in five samples from the contact metamorphosed Biwabik Iron Formation. These samples attained peak metamorphic temperatures of <200, <340,~500, <550, and <740°C respectively. d 56 Fe of bulk layers ranges from-0.8 to +0.8&; in some samples the layers may differ by >1& on the millimeter scale. Minerals in the lowest grade samples consistently show a sequence in which d 56 Fe of magnetite > silicate ‡ carbonate. The intermine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(57 citation statements)
references
References 70 publications
(104 reference statements)
2
54
1
Order By: Relevance
“…In the Old Wanderer BIF, magnetite -siderite pairs show a relative difference of ~0.9‰. Very similar values have been reported for the Kuruman BIF in the Transvaal Basin, South Africa , and the Biwabik BIF (Frost et al, 2007) which have been interpreted as resulting from a coupled diagenetic formation process of siderite and magnetite due to DIR. Experimental work by Johnson et al (2005) has revealed an equilibrium fractionation factor ∆ siderite-magnetite of -1.3‰ for DIR, whereas Johnson et al (2008) prefer a fractionation factor of -1.8‰ (see Table 5).…”
Section: Diagenesis and The Formation Of Magnetite And Iron Carbonatesupporting
confidence: 75%
See 3 more Smart Citations
“…In the Old Wanderer BIF, magnetite -siderite pairs show a relative difference of ~0.9‰. Very similar values have been reported for the Kuruman BIF in the Transvaal Basin, South Africa , and the Biwabik BIF (Frost et al, 2007) which have been interpreted as resulting from a coupled diagenetic formation process of siderite and magnetite due to DIR. Experimental work by Johnson et al (2005) has revealed an equilibrium fractionation factor ∆ siderite-magnetite of -1.3‰ for DIR, whereas Johnson et al (2008) prefer a fractionation factor of -1.8‰ (see Table 5).…”
Section: Diagenesis and The Formation Of Magnetite And Iron Carbonatesupporting
confidence: 75%
“…The investigation of fractionation mechanisms of stable Fe isotopes is now well-advanced, and shows an overall range of ~5 ‰ in  56 Fe (for overview see Anbar, 2004;Beard and Johnson, 2004;Dauphas and Rouxel, 2006). The largest variability in the Fe isotope composition in any single type of sample has so far been measured in BIFs Dauphas et al, 2004Dauphas et al, , 2007Rouxel et al, 2005;Frost et al, 2007;Whitehouse and Fedo, 2007;Valaas Hyslop et al, 2008) and ranges from about -2.5 to 1.6‰ in  56 Fe. It has been shown that Fe isotope heterogeneities in BIFs can be preserved during diagenesis and metamorphism (Frost et al, 2007;Whitehouse and Fedo, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With that said, although petrographically most siderite (and ankerite) exhibit recrystallised and, therefore, apparently secondary textures, their geochemistry does indicate that some potentially "primary" signals can be retained in IF carbonates. Iron isotopes of extracted carbonate fraction remained unaffected by low-grade metamorphism (Frost et al, 2007) and carbonate-specific REE+Y patterns, both in situ (Alibert, 2016) and extracted as bulk (Oonk, 2017), mimic REE+Y aspects of present-day seawater.…”
mentioning
confidence: 92%